FENOMENA PARKIR SEWA - Mahanggi, Muh. Rizal (Universitas Bina Taruna Gorontalo, 2015)
ABSTRACK The study aims to explore and acquire for thoughts and based on the conception of Local about parking phenomenon Rent in Environmental Kauman Regarding research methods will discuss research paradigm , location research , case studies , tools and energy used , the research and analysis process . The study used research hearts husband is phenomenology . Phenomenological paradigm requires researchers down- to Field Theory armed Without A Solid , researchers Must feel Alone object Yang studied thus able to find phenomena - phenomena. Only researchers have investigated the understanding about object The Astra Honda Motor hearts as background knowledge to understand the phenomena - phenomena in the field . Keywords : parking rent.